In vivo monitoring of transfected DNA, gene expression kinetics, and cellular immune responses in mice immunized with a human NIS gene-expressing plasmid. (December 2016) - Son, Hye-Youn; Jeon, Yong-Hyun; Chung, June-Key; Kim, Chul-Woo
In assessing the effectiveness of DNA vaccines, it is important to monitor: (1) the kinetics of target gene expression in vivo ; and (2) the movement of cells that become transfected with the plasmid DNA used in the immunization of a subject. In this study, we used, as a visual imaging marker, expression of the transfected human sodium/iodide symporter ( hNIS ) gene, which enhances intracellular radio-pertechnetate (TcO4–) accumulation. After intradermal (i.d.) and systemic injection of mice with pcDNA-hNIS and radioactive Technetium-99m (Tc-99m), respectively, whole-body images were obtained by nuclear scintigraphy. The migration of mice cells transfected with the hNIS gene was monitored over a 2-week period by gamma-radioactivity counting of isolated cell populations and was demonstrated in peripheral lymphoid tissues, especially in the draining lymph nodes (dLNs). Beginning at 24 h after DNA inoculation and continuing for the 2-week monitoring period, hNIS -expressing cells were observed specifically in the T-cell–rich zones of the paracortical area of the dLNs. Over the same time period, high levels of INF-γ–secreting CD8 T-cells were found in the dLNs of the pcDNA-hNIS immunized mice. Tumor growth was also significantly retarded in the mice that received hNIS DNA immunization followed by inoculation with CT26 colorectal adenocarcinoma cells that had been transfected with the rat NIS gene ( rNIS ), which is 93% homologous to the hNIS gene. In conclusion, mouse cells transfected with hNIS DNA after i.d. immunization were found to traffic to the dLNs, and hNIS gene expression in these cells continued for at least 2 weeks post immunization. Furthermore, sequential presentation of NIS DNA to T-cells by migratory antigen presenting cells could induce NIS DNA-specific Th1 immune responses and thus retard the growth of NIS -expressing tumors.